FACTORS INFLUENCING THE OUTCOME OF LUMBAR PUNCTURES. ARE WE LOSING OUR SKILL SET?. Issue 12 (15th November 2016) - McCloskey, Ryan; Michael, Ben; Panicker, Jay; Bonello, Michael
Abstract : Objectives: To identify which factors influence the successful outcome of lumbar punctures (LP) carried out on an elective basis at a tertiary referral centre. Methods: A retrospective analysis of 50 patients who underwent elective LPs on the elective day unit in May and June 2015 was carried out analysing factors including age, gender, BMI, indication for the procedure and the grade of the physician performing the procedure. The outcome measure was an unsuccessful LP, defined as no quantifiable CSF. Results: 46 patients were included and of these 11 were unsuccessful. There was a strong correlation with a reduction in the success of an LP as BMI increased R2 (p<0.02). The number of attempts also increased with a higher BMI R2 (p<0.01). The grade of physician performing the procedure, age, sex and indication did not predict unsuccessful LPs. Conclusion: BMI is shown to be the factor that most dictates the outcome of the LP on an elective basis. It would be prudent to explore the influence of physician grade further, as our data confirmed a trend but this was not statistically significant. The identification of measures which result in unsuccessful LPs should help improve a pathway for direct referral to radiologically assisted CSF taps.